Computer Simulations of Nanostructured Carbon Under Tensile Load: Electronic Structure and Optical Gap - Mathioudakis, Christos; Fyta, Maria G. (My University, 2012)
We use computer simulations to study the behavior of amorphous carbon and carbon composites under tensile strain. We investigate the behavior of the optoelectronic properties of these materials as strain is increased. These properties are monitored through the electronic density of states, the optical gap and the Urbach energy for both materials. The variation in the hybrid (sp 2 and sp 3) content due to the external load is directly connected to changes in the optoelectronic properties with increasing strain. This connection will lead to interesting features in the Urbach edge for the amorphous network, while the respective effect for the nanocomposite will be less pronounced. The situation is reversed when the optical gap is used as a probe of the properties of both amorphous and composite materials.
Keywords: Amorphous carbon; Coatings; Composites; Diamond crystal; Nanocrystalline; Optical properties; Optoelectronic properties; Simulation; Strain